THE EFFECT OF ENGAGEMENT ON EMPLOYEE PERFORMANCE THROUGH THE IMPLEMENTATION OF LEADERSHIP - Budi Susilo; Syaifuddin; Sofiyan (Yayasan Nuraini Ibrahim Mandiri, 2026)
The decline in the quality of a plantation company is often caused by various factors, both internal and external to the company itself. The main objective of this study is to determine the effect of engagement on leadership implementation and employee performance at PTPN IV Regional 1, both directly and indirectly through the mediation of leadership implementation. The analytical method used in this study was Structural Equation Modeling (SEM) based on SmartPLS version 4.1. The research population is all employees of PTPN IV Regional 1. The sampling technique used was cluster random sampling, and the sample size was calculated using the Slovin formula. This resulted in 391 employees from three employee groups at PTPN IV Regional 1, selected proportionally. The results indicate that engagement directly has a positive and significant effect on leadership implementation and employee performance. Furthermore, leadership implementation plays a significant role in mediating the relationship between the independent variables and employee performance, thereby strengthening the influence of organizational factors on performance. The implications of this study indicate that increasing engagement that supports innovation can strengthen leadership implementation at PTPN IV Regional 1, thereby improving employee performance and supporting the achievement of organizational goals.